Comprehensive analysis of TGF-β-induced mRNAs and ncRNAs in hepatocellular carcinoma - Liang, Junnan (Aging (Albany NY), 2020)
Transforming growth factor β (TGF-β) is a potent inducer of epithelial-mesenchymal transition (EMT) in hepatocellular carcinoma (HCC), and plays a critical role in its tumorigenesis and progression. Accumulating evidence indicates that protein-coding mRNAs, as well as non-coding RNAs (ncRNAs), may play key roles in the tumorigenesis and progression of HCC. In this study, we first report on the differential expression of lncRNAs, mRNAs, miRNAs, and circRNAs in Huh7 cells treated with TGF-β or DMSO for 7 days. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed for significantly differentially expressed RNAs (DE RNAs). Then the competing endogenous RNA (ceRNA) network based on these DE RNAs was predicted and constructed. Among them, we identified that lncRNA SLC7A11-AS1 and hsa_circ_0006123 are involved in the EMT process induced by TGF-β and may promotes the metastasis of HCC. This knowledge may pave the way to develop novel clinical diagnostics and therapeutic approaches. Our study might open a new avenue for future investigations of the molecular mechanisms driving the EMT process induced by TGF-β in HCC.